The action of somatostatin on neurones of the myenteric plexus of the guinea-pig ileum. - Katayama, Y (1980)
1. Intracellular recordings were made from neurones in ganglia of the myenteric plexus of the guinea-pig ileum. 2. Somatostatin (10-300 nM) was applied to the neurones by adding it to the perfusing solution or by ejecting it (charges up to 500 nC) from an ionophoresis electrode onto the soma membrane. 3. By both methods of application, somatostatin either hyperpolarized or depolarized a proportion of neurones. Depolarizing responses were more often observed with ionophoretic application, and hyperpolarizing responses were more often observed with application by perfusion. Both responses were preserved in solutions containing zero Ca and elevated (6 mM) Mg. Some cells were both hyperpolarized and depolarized, depending on the method of administration. 4. The depolarizing responses to somatostatin were associated with an increase in cell input resistance; they became larger with membrane depolarization and smaller with membrane hyperpolarization, and reversed in polarity at a potential close to the potassium equilibrium potential. The hyperpolarizing responses to somatostatin were accompanied by a fall in cell input resistance.